The non-Markovian Fokker–Planck kinetic equation for a system of hard spheres - Gapyak, I.V.; Gerasimenko, V. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
For a many-particle system composed of a tracer hard sphere and an environment of hard spheres with elastic collisions, the generalized Fokker–Planck kinetic equation is justified. The scaling approximations of a solution of the constructed kinetic equation are considered.